2005
DOI: 10.3168/jds.s0022-0302(05)72860-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat Stress on Production of Mediterranean Dairy Sheep

Abstract: RIASSUNTO -Effetto delloKEY WORDS: heat tolerance, temperature-humidity index (THI), dairy sheep.INTRODUCTION -European Mediterranean countries are characterized by exposure to considerable heat between three and six months annually. High ambient temperature, solar radiation, wind speed and relative humidity, cause the effective temperature of the environment to be above the thermo-neutral zone of the animals (5 to 25ºC; McDowell, 1972) and therefore heat stress occurs (Bianca, 1962). Heat stress is one of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(65 citation statements)
references
References 11 publications
7
49
1
2
Order By: Relevance
“…This temperature increase can negatively affect the physiology and performances of this breed in a similar manner to that which has been reported to affect other dairy animals (West, 2003). The economic consequence of heat stress has already been identified for Murciano-Granadina and Payoya goats in Spain (Menéndez-Buxadera et al, 2012) and similar effects were also reported for milk yield in Valle del Belice dairy sheep in Palermo, Italy (Finocchiaro et al, 2005). Moreover, both groups of authors found important genetic variation in response to heat stress.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…This temperature increase can negatively affect the physiology and performances of this breed in a similar manner to that which has been reported to affect other dairy animals (West, 2003). The economic consequence of heat stress has already been identified for Murciano-Granadina and Payoya goats in Spain (Menéndez-Buxadera et al, 2012) and similar effects were also reported for milk yield in Valle del Belice dairy sheep in Palermo, Italy (Finocchiaro et al, 2005). Moreover, both groups of authors found important genetic variation in response to heat stress.…”
Section: Introductionsupporting
confidence: 70%
“…This made it possible to quantify the reaction norm or plasticity of each trait -an old biological concept recently reviewed by de Jong and Bijma (2002). Random regression models were used for these analyses in dairy cattle (Bohmanova et al, 2005(Bohmanova et al, , 2008Aguilar et al, 2009;Brugemann et al, 2011;Bernabucci et al, 2014;Hammami et al, 2013), dairy sheep (Finocchiaro et al, 2005) and dairy goats (Menéndez-Buxadera et al, 2012). The application of the random regression models to solve different types of problems in animal breeding was reviewed by Schaeffer (2004).…”
Section: Introductionmentioning
confidence: 99%
“…Milk production traits in ewes seem to have higher negative correlation with the direct values of temperature or relative humidity than THI. The values of THI above which ewes start to suffer from HS seem to be quite different among sheep breeds (Finocchiaro et al, 2005). Solar radiation seems to have a lesser effect on milk yield, but a greater effect on yield of casein, fat and clot firmness in the milk of Comisana ewes (Sevi et al, 2001).…”
Section: Other Speciesmentioning
confidence: 95%
“…The authors reported significant differences between animals due to breed, skin type and time of the day and concluded the Santa Inês (hair sheep) with white color were shown to be better adapted to higher environmental temperatures while Bergamasca, wool sheep, were least adapted. Finocchiaro et al (2005) reported the genetic correlation between the general additive effect of milk production and the additive effect of heat tolerance to be negative (r = −0.8) during all periods considered indicating that selection for increased milk production will reduce heat tolerance. Turner (1980) extensively reviewed the genetic and biological aspects of zebu adaptability and attributed their unique suiting to hot climates to coat, hide, skin, hematological characteristics, form, growth, and physiological aspects which are unique genetic attributes of zebu compared to Bos taurus cattle.…”
Section: Adaptation To Severe (Hot/cold) Climatesmentioning
confidence: 99%